An insect-inspired bionic sensor for tactile localization and material classification with state-dependent modulation - Patanè, Luca; Hellbach, Sven; Krause, André F.; Arena, Paolo; Dürr, Volker (Frontiers in Neurorobotics, 2012)
Insects carry a pair of antennae on their head: multimodal sensory organs that serve a wide range of sensory-guided behaviours. During locomotion, antennae are involved in near-range orientation, for example in detecting, localising, probing and negotiating obstacles. Here we present a bionic, active tactile sensing system inspired by insect antennae. It comprises an actuated elastic rod equipped with a terminal acceleration sensor. The measurement principle is based on the analysis of damped harmonic oscillations registered upon contact with an object. The dominant frequency of the oscillation is extracted to determine the distance of the contact point along the probe, and basal angular encoders allow tactile localisation in a polar coordinate system. Finally, the damping behaviour of the registered signal is exploited to determine the most likely material. The tactile sensor is tested in four approaches with increasing neural plausibility: First, we show that peak extraction from the Fourier spectrum is sufficient for tactile localisation with position errors below 1%. Also, the damping property of the extracted frequency is used for material classification. Second, we show that the Fourier spectrum can be analysed by an Artificial Neural Network which can be trained to decode contact distance and to classify contact materials. Thirdly, we show how efficiency can be improved by band-pass filtering the Fourier spectrum by application of non-negative matrix factorisation. This reduces the input dimension by 95% while reducing classification performance by 8% only. Finally, we replace the FFT by an array of spiking neurons with gradually differing resonance properties, such that their spike rate is a function of the input frequency. We show that this network can be applied to detect tactile contact events of a wheeled robot, and how detrimental effects of robot velocity on antennal dynamics can be suppressed by state-dependent modulation of the input signals.